PROKRASTINASI AKADEMIK MENGHAMBAT PENINGKATAN PRESTASI AKADEMIK REMAJA DI WILAYAH PERDESAAN - Zahra, Yuana; Hernawati, Neti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
Academic achievement is one of the indicators to determine the success of educational goals. This research was to analyze the influence of adolescent characteristics, family characteristics, peer group behavior, selfefficacy,and academic procrastination on academic achievement of adolescent. This study was conducted in Bogor regency, West Java Province. The number of samples in this study were 150 high school students that were chosen by proportional random sampling. Self-efficacy was measured by Indonesian Adaption of General Self Efficacy Scale’s instrument. Academic procrastination was measured by using Tuckman Procrastination Scale. Data was collected by self report and was analyzed by descriptive analysis, correlation test, and multiple linear regression test. The result showed that the role of peer correlated significantly with self efficacy and self efficacy corellated significantly with academic procrastination. The academic achievement of adolescent wasinfluenced positively by sex and peers behavior (role and action of peers) and negatively was influenced by academic procrastination.